2017
DOI: 10.21474/ijar01/5869
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Ethyl Acetate Fraction of Cocos Nucifera Root Extract.

Abstract: 1083Cocos nucifera is a tropical coastal plant. The ethyl acetate fraction of its aqueous root extract stimulates erythropoiesis. This work aimed to evaluate the biological tolerance of this fraction. The extract fraction was administered to Wistar rats at a single dose of 2000 mg / kg body weight for Acute Oral Toxicity (OAT) or in daily doses of 200 mg / kg body weight for 28 days for Sub-Chronic Toxicity. (SCT), as recommended by the OECD. On day 0, then on day 14 for OAT and day 28 for SCT, the rats were w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 8 publications
8
9
2
Order By: Relevance
“…This result was better than that of the crude aqueous extract of Psorospermumfebrifugum, which minimum dose corrected the hemoglobin level only at day 15 (Agbogba et al, 2019a). On the other hand, it confirmed that observed with the ethyl acetate fraction of Cocos nucifera root aqueous extract (Sènou et al, 2017c). At day 15, the hemoglobin level was significantly greater than its D0 value only in the group receiving the 60 mg dose of extract / Kg (high dose) suggesting a dosedependent effect.…”
Section: Discussion:-supporting
confidence: 86%
See 1 more Smart Citation
“…This result was better than that of the crude aqueous extract of Psorospermumfebrifugum, which minimum dose corrected the hemoglobin level only at day 15 (Agbogba et al, 2019a). On the other hand, it confirmed that observed with the ethyl acetate fraction of Cocos nucifera root aqueous extract (Sènou et al, 2017c). At day 15, the hemoglobin level was significantly greater than its D0 value only in the group receiving the 60 mg dose of extract / Kg (high dose) suggesting a dosedependent effect.…”
Section: Discussion:-supporting
confidence: 86%
“…Mean cell volume(MCV) increased in all anemic groups with a peak on day 7 in the anemic and treated groups indicating early release into the bloodstream of macrocytes, immature red blood cells to compensate for anemia [31]. The globular volume then decreased progressively in the treated groups and at J15 no longer differed significantly from D0, indicating a well-differentiated red blood cells release at the end of the experimental period.…”
Section: Discussion:-mentioning
confidence: 96%
“…For this purpose, we fractionated the extract in order to test some of its fractions. One of the fractions that we wanted to test was that of ethyl acetate because this fraction of the aqueous extract of Cocos nucifera showed a good hematopoietic activity (Sènou et al, 2017a). But first, it should first ensure the safety of this fraction of the extract before testing its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 80% of people in poor countries use traditional medicine. The main reason was the high price of pharmaceutical drugs (Schmincke, 2003;Yakubu et al, 2009;Pingali et al, 2015). Therefore, many plants are used against anemia, some of which are very effective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation